Developing a novel integrated geriatric palliative care consultation program for the emergency department. Issue 6 (11th December 2022) - Stoltenberg, Mark J.; Kennedy, Maura; Rico, Janet; Russell, Matthew; Petrillo, Laura A.; Engel, Kirsten G.; Kamdar, Mihir; Ouchi, Kei; Wang, David H.; Bernacki, Rachelle H.; Biese, Kevin; Aaronson, Emily
Abstract: With the aging of our population, older adults are living longer with multiple chronic conditions, frailty, and life‐limiting illnesses, which creates specific challenges for emergency departments (EDs). Older adults and those with serious illnesses have high rates of ED use and hospitalization, and the emergency care they receive may be discordant with their goals and values. In response, new models of care delivery have begun to emerge to address both geriatric and palliative care needs in the ED. However, these programs are typically siloed from one another despite significant overlap. To develop a new combined model, we assembled stakeholders and thought leaders at the intersection of emergency medicine, palliative care, and geriatrics and used a consensus process to define elements of an ideal model of a combined palliative care and geriatric intervention in the ED. This article provides a brief history of geriatric and palliative care integration in EDs and presents the integrated geriatric and palliative care model developed.